Novel thrombolytic protease from the rare halophile Brachybacterium paraconglomeratum: bioprocessing and in vitro application - Mandragutti Teja; Tura Safawo Jarso; Dokka Muni Kumar; Sudhakar Godi (BMC Biotechnology)
Abstract Background Alkaline proteases are hydrolytic enzymes that play a crucial role in various biological processes. Proteases produced by halophiles showed exceptional efficiency in breaking down the complex structures ranging from pigments to extracellular proteins, tissue proteins to tumors, and thrombin clots. There is a huge global demand for naturally occurring thrombolytic proteases to treat intravascular thrombosis, as they are cost-effective and have minimal detrimental effects, making them widely used in the biomedical applications. Results The production of thrombolytic protease from the rare halophile Brachybacterium paraconglomeratum strain M4 and its in-vitro thrombolytic activity is investigated for the first time. On skim milk agar, a distinct zone of casein hydrolysis was observed, in submerged fermentation a substantial protease production was noted. The enzyme was purified through a four-step purification process following an initial precipitation with 60% ammonium sulfate, subsequent ion-exchange chromatography using DEAE-cellulose, and final gel-filtration chromatography utilizing Sephadex G-100. As a result, a protein with a specific activity of 300 ± 32 U/mg was obtained with a purification fold of 19 and a recovery percentage of 38.2%. The molecular mass of the purified enzyme was 14.4 kDa via SDS-PAGE while MALDI/MS analysis further revealed a 131 amino acid sequence with an isoelectric point of 8.55 and on comparison, the strain M4 alkaline protease aligns with the proteasome subunit alpha. The protease is classified as a serine protease based on the inhibition by PMSF and its activity profile. The in-vitro thrombolytic assay revealed that the purified enzyme achieved a clot lysis rate of 65 ± 3%, performing effectively in comparison to the standard. Conclusion The findings indicate that strain M4 is an efficient producer of thrombolytic protease and the purified form effectively dissolves thrombin clots. Currently, the studies are underway to explore its potential for biomedical applications and industrial-scale production.